Far‐travelled ash in past and future eruptions: combining tephrochronology with volcanic studies. (10th November 2019) - Cashman, Katharine V.; Rust, Alison C.
ABSTRACT: Studies of recent eruptions have improved our understanding of volcanic ash transport and deposition, but have also raised important questions about the behaviour of far‐travelled (distal) volcanic ash. In particular, it is difficult to reconcile estimates of distal ash mass and transport distance determined from eyewitness accounts, mapped deposits, satellite‐based observations and cryptotephra records. Here we address this problem using data from well‐characterized eruptions that, collectively, include all four data types. Data from recent eruptions allow us to relate eyewitness accounts to mapped deposits on the ground and satellite‐based observations of ash in the air; observations from an historical eruption link eyewitness accounts to cryptotephra deposits. Together these examples show that (i) 10–20% of the erupted mass is typically deposited outside the mapped limits; (ii) estimates of the ash mass transported in volcanic clouds cannot account for all of this unmapped ash; and (iii) ash fall observed at distances beyond mapped deposits can have measurable impacts, and can form cryptotephra deposits with high (> 1000 cm −3 ) shard counts. We conclude that cryptotephra data can be incorporated into volcanological studies of ash transport and deposition and provide important insight into both the behaviour and impacts of far‐travelled volcanic ash particles.